Melamine Processing and Mathematical Modelling of Melamine Drying in Wood - Sugiyanto, Sugiyanto (Kaunia: Integration and Interconnection Islam and Science Journal, 2020)
Melamine wood is a coating that makes wood shiny. In this model, the Moisture Ratio formula is obtained from the melamine process. The formula is MR=a+bt, where a and b are empirical constants in drying models and values a and b depending on the ambient temperature.